2018
DOI: 10.1111/jsbm.12380
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Top Management Participation and IT Capability in Developing SMEs’ Competitive Process Capabilities

Abstract: This research explores how top management participation and three types of IT capability enable SMEs' competitive process alignment and flexibility capabilities. Our research hypotheses are tested using data from 310 Australian SMEs. Results show that top management participation and external IT linkage capability positively affect both process alignment and process flexibility. While IT infrastructure capability and IT business spanning capability positively affect process alignment, they are not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 99 publications
(167 reference statements)
1
16
1
2
Order By: Relevance
“…Using Korean steel suppliers as their sample, Youn et al [48] found that the competitive advantage of the Korean steel industry is heavily influenced by the supply chain inter-organizational information system capabilities. Several empirical studies have shown a positively significant linkage between information system capabilities and the competitive process alignment and flexibility capabilities of small to medium-sized enterprises (SME) [49][50][51]. Using data collected from Australian retailing sectors, Rajaguru and Matanda [6] found that inter-organizational information system integration and supply chain capabilities were facilitated by cultural inter-organizational factors and inter-organizational technical and strategic compatibility.…”
Section: Supply-chain Management Systemsmentioning
confidence: 99%
“…Using Korean steel suppliers as their sample, Youn et al [48] found that the competitive advantage of the Korean steel industry is heavily influenced by the supply chain inter-organizational information system capabilities. Several empirical studies have shown a positively significant linkage between information system capabilities and the competitive process alignment and flexibility capabilities of small to medium-sized enterprises (SME) [49][50][51]. Using data collected from Australian retailing sectors, Rajaguru and Matanda [6] found that inter-organizational information system integration and supply chain capabilities were facilitated by cultural inter-organizational factors and inter-organizational technical and strategic compatibility.…”
Section: Supply-chain Management Systemsmentioning
confidence: 99%
“…However, to make decisions regarding flexibility in product/service development, firms require technologies and information systems that provide key information to support those decisions. ICT capabilities also involve the owner's, manager's or area manager's abilities to access and analyze information obtained from digital platforms or systems, allowing him/her thereby to make timely decisions regarding the creation/design/change of processes, products or services and to respond to customer demands (Bi et al 2019 ). Given the above, in this study, we postulate that ICT capabilities can foster the flexibility to rapidly design/produce new products/services and influence the innovation performance of firms.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In this sense, some recent studies show that the development of these technological capabilities is catalyzing/supporting the development of other more complex capabilities (Soto-Acosta et al 2018 ; Cai et al 2019 ; Felipe et al 2020 ), denoting thereby the integration or complementarity between various resources/capacities of the company. In fact, it is well known that organizational capabilities are integrated or complemented by other capabilities of varying complexity, allowing companies to achieve competitive advantages over the competition and improve performance (Ennen and Richter 2010 ; Bi et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation through alliances, for example, can enable SMEs to survive under high environmental uncertainty and rapid technological obsolescence because external knowledge flows enhance internal learning and keep SMEs flexible (Hoffmann and Schlosser 2001). These knowledge flows and further external relationships enable SMEs to align and adapt internal processes (Bi et al 2018). For these reasons, cooperative relationships can be considered as a driver for organizational agility in a business environment that is characterized by dynamic change and uncertainty.…”
Section: Cooperative Relationships and Organizational Agilitymentioning
confidence: 99%